Reintegrasi Sosial Dalam Sistem Pemasyarakatan Sebagai Visi Pemidanaan Dalam Hukum Nasional - Sri Wulandari (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
The government has stipulated RI Law no. 1 of 2023 concerning the Criminal Code (KUHP) as a form of legal political policy in social, national and state life that upholds Human Rights (HAM). The material of the National Criminal Code regulates the balance between the interests of victims and perpetrators, in line with restorative justice and not based on retributive theory, namely crime as a means of revenge. Even though the perpetrator of a criminal act is subject to sanctions/punishment, these "sanctions" are a correction of the mistakes committed. This research aims to analyze the concept of social reintegration in the correctional system as a vision of punishment in national law. Using secondary data sources supported by primary data, it is then presented in a qualitative descriptive manner. The development of prisoners in correctional institutions (Lapas) is based on a rehabilitative philosophy (UU No. 12 of 1995 Jo. UU No. 22 of 2022), namely the aim of punishment is to return criminals to society and to reduce the tendency to be involved in crime in the future. Meanwhile, the vision of punishment in national law is Social Reintegration as a replacement for the concept of retaliation or deterrence where perpetrators of criminal acts are given a second (2) chance to become good human beings, it is hoped that after serving the sentence they can return to society and not repeat the crime. This concept also strengthens the concept of restorative justice adopted in the Juvenile Criminal Justice System and the renewal of national criminal law.